Forming AkhlÄqul KarÄ«mah (Noble Character) of the Students of Institute of Islamic and Arabic Language (STIBA) Makassar by Implementing Tarbiyah IslÄmiyah (Islamic Education) Program - M. Kasim; Azwar Azwar (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to: (1) analyze the effect of implementing tarbiyah rÅ«hiyah on akhlÄqul karÄ«mah in Makassar STIBA students; (2) analyze the effect of implementing tarbiyah á¹¡aqÄfiyah on akhlÄqul karÄ«mah in Makassar STIBA students; and (3) analyzing the influence of the implementation of jasadiyah tarbiyah on akhlÄqul karÄ«mah in Makassar STIBA students. This study uses data obtained from respondents through questionnaires and a quantitative approach through the component-based Structural Equation Modeling (SEM) technique or variant with Partial Least Square (PLS). The results showed that: (1) the implementation of tarbiyah rÅ«hiyah had a positive and significant effect on akhlÄqul karÄ«mah for STIBA Makassar students; (2) the implementation of tarbiyah á¹¡aqÄfiyah has a positive and significant effect on the akhlÄqul karÄ«mah of STIBA Makassar students; and (3) the implementation of tarbiyah jasadiyah has a positive and significant effect on akhlÄqul karÄ«mah for STIBA Makassar students. Therefore, as a policy recommendation, fostering student akhlÄqul karÄ«mah in tertiary institutions can be carried out through the Islamic tarbiyah program as an extracurricular activity. The application of student akhlÄqul karÄ«mah coaching can be done through integration into the lecture process. Interventions for the implementation of the Islamic tarbiyah program in tertiary institutions can be applied by making rules and signs for akhlÄqul karÄ«mah both on campus and outside the campus